Effects of rubber production promotion on intrahousehold gender relations : a case study of Katus in Thua Thien Hue Province, Vietnam - Ngo Thi Thuan; Kusakabe, Kyoko; Earth, Barbara; Ahmad, Mokbul Morshed; Government of Norway (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
Rubber plantation is one of strategic policies of Vietnam government in socio-economic development of remote and mountainous areas in terms of income generation and improvement of living standard. Although Katu women play important roles in rubbergrowing household production and reproduction activities, they still have low status and get less benefit from rubber income. Addressing these issues, the research analyzes socioeconomic characteristics of Katu rubber-planting households to examine changes in household income, intra-household allocation and gender relations. Focusing on Huong Son commune of Katu ethnic minority in Nam Dong district, Thua Thien Hue province in the Central Vietnam, this study aims to explore and address the changes in gender division of labor, access to resources and decision making in Katu households. It is found that with rubber cultivation, household income increased for some of rubber growing households whereas the others decreased their income due to land sparing for currently unproductive rubber. A comparison between group of households getting rubber income and another group of rubber planting households without having income from rubber revealed that women bear more burdens and longer working time in regards to their triple roles but get less access to resources and fewer benefits compared with men. Meanwhile, in coping with shortage of food, women promote their ability in managing crop production for household food subsistence. As the result, women get better position in family as a major labor for food. The study also identified that women were facing various types of problems deriving from rubber plantation and constraints related with Katu patriarchal norms and customs. Finally, some recommendations are raised how to make policies gender responsive and to release women discrimination as well as to improve their status in Katu society to date.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2006
Keywords: Rubber plants -- Social aspects -- Vietnam -- Thua Thien Hue; Rubber plants -- Economic aspects -- Vietnam -- Thua Thien Hue